An introduction to developmental psychology - Slater, Alan; Bremner, J. Gavin (b, 2017)
* A representative and authoritative 'state of the art' account of human development from conception to adolescence. * Written at an easy-to-comprehend level by an international team of respected researchers, conveying their knowledge with enthusiasm and skill.
Includes bibliographical references and index.
Keywords: Developmental psychology